The Use of the Treagust Strategy to Promote Enthusiasm for Learning Science Subjects and the Growth of Scientific Ideas in Primary School Students - Alanazi, F. H. (Jurnal Pendidikan IPA Indonesia, 2022)
This study examines the effect of the Treagust strategy on the development of an understanding of science concepts in Saudi primary school students and on developing an understanding of science concepts in Saudi primary school students and promoting their motivation to learn science. A quasi-experimental design (i.e., one experimental group) was adopted, and pre- and post-learning measurements were administered. The sample consisted of 13 fifth-grade students. The instruments tools of the study were the Science Achievement Test and the Motivation towards Learning Science Scale. The overall results indicated that the programme was effective in improving effectively improved science achievement, as there was a significant difference between the mean scores of the pre- and post-learning measurements at the 0.01 level in the MCQ test, favoring the post-learning measurement. Furthermore, statistically significant differences were found between the pre- and post-learning measurements in the dimensions of self-esteem, performance, and achievement; the only insignificant subscale was the value of learning science. The research concludes with a presentation and discussion of recommendations and future research topics in light of the findings.